2020
DOI: 10.3390/ijerph17134820
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control Moderates the Association Between Perceived Severity of Coronavirus Disease 2019 (COVID-19) and Mental Health Problems Among the Chinese Public

Abstract: Coronavirus disease 2019 (COVID-19) has caused thousands of deaths in China. Prior research suggests that individuals’ perceived severity of COVID-19 is related to a range of negative emotional and behavioral reactions among the Chinese public. However, scant research has examined the underlying mechanisms. Drawing upon the risk-resilience model, this study proposes that self-control, as a resilient factor, would potentially moderate the association between perceived severity of COVID-19 and mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 31 publications
5
119
0
6
Order By: Relevance
“…Although a lockdown increases the chance of effectively dealing with COVID-19, it also contributes to a decrease in people's well-being [1][2][3][4], invoking several adverse emotional reactions such as anger, fear, confusion, irritability, frustration, elevated stress, insomnia, and nervousness [1,4,5]. Thousands of people have lost their work and socio-economic status during the COVID-19 pandemic.…”
Section: Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a lockdown increases the chance of effectively dealing with COVID-19, it also contributes to a decrease in people's well-being [1][2][3][4], invoking several adverse emotional reactions such as anger, fear, confusion, irritability, frustration, elevated stress, insomnia, and nervousness [1,4,5]. Thousands of people have lost their work and socio-economic status during the COVID-19 pandemic.…”
Section: Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%
“…(3) Has the level of PA changed from before the pandemic? (4) What is the association between PA, anxiety, and depression in the study sample? Due to differences between the sexes found in previous studies on PA, anxiety, and depression during the COVID-19 pandemic, sex will be controlled in this study as a covariate.…”
Section: Physical Activity and Healthmentioning
confidence: 99%
“…Public places and schools were briefly re-opened in late May, only to be shut down a few weeks later when the third wave of virus outbreak hit the city (surging new cases had been documented since June 22nd). Such prolonged isolation and changes of daily routine are likely to cause psychological and emotional distress among the public and students [4][5][6][7]. One possible reason is that disease control measures such as social isolation make it more difficult for people to satisfy one of their fundamental psychological needs, that of belongingness [14].…”
Section: Depressive Symptoms and Peer Relationships In The Time Of Pamentioning
confidence: 99%
“…To recap, under the impact of COVID-19, individuals around the globe have been experiencing psychological problems such as elevated depressive symptoms [4][5][6][7]. Some public health measures such as school closures and social distancing helped contain the spread of virus, but also prevented people, especially students, from satisfying their need to connect to others.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation